Framing effects as a semantic puzzle: Putting the alignment-assumption account to a test - Claus, Berry (Proceedings of Sinn und Bedeutung, 2019)
Framing effects are effects of linguistic variation (e.g. stating the amount of lives saved vs. lives lost) on judgments and decisions. This paper deals with a semantic-pragmatic account of framing effects as offered by Geurts’ (2013) alignment-assumption account. The account radically differs from extant accounts by explaining framing effects in terms of counterfactual alternatives and alignment of scales. I report two experiments that tested predictions derived from the alignment-assumption account and that related to the effect of upward- vs. downward entailing comparative quantifiers. The results provide preliminary experimental support for the alignment-assumption account and pose challenges for other accounts of framing effects.